2021
DOI: 10.1016/j.isci.2021.102537
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the long non-coding RNA OIP5-AS1 exacerbates heart failure in a sex-specific manner

Abstract: Summary Long non-coding RNAs (lncRNAs) have been demonstrated to influence numerous biological processes, being strongly implicated in the maintenance and physiological function of various tissues including the heart. The lncRNA OIP5-AS1 ( 1700020I14Rik /C yrano ) has been studied in several settings; however its role in cardiac pathologies remains mostly uncharacterized. Using a series of in vitro and ex vivo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…We have previously described a global Oip5os1 null mouse generated by our laboratory, which demonstrated no detectable expression of Oip5os1 in all tissues analyzed (Zhuang, Calkin, et al., 2021). In brief, the entire genomic location (~13 kb) of this gene was removed in the KO mice, covering everything from the transcriptional start site, all exons and introns, and ending at the final codon of the last exon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described a global Oip5os1 null mouse generated by our laboratory, which demonstrated no detectable expression of Oip5os1 in all tissues analyzed (Zhuang, Calkin, et al., 2021). In brief, the entire genomic location (~13 kb) of this gene was removed in the KO mice, covering everything from the transcriptional start site, all exons and introns, and ending at the final codon of the last exon.…”
Section: Resultsmentioning
confidence: 99%
“…Oip5os1 knockout (KO) mice were generated in our laboratory on a C57BL/6J background with the Australian Phenomics Network as previously described (Zhuang, Calkin, et al., 2021). Mice were bred as heterozygous parental lines and cohorts of littermate wildtype (WT), and KO mice were generated for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Among the differentially expressed lncRNAs identified ( Tables 1 , 2 ), Oip5os1 (OIP5-AS1, transcript ID: ENSMUST00000147425, FC = 115.55), UBXN7 (transcript ID: chr16: 32388756-32392334, FC = 101.58), and Snhg12 (transcript ID: ENSMUST00000128131, FC = 44.14) exhibited significantly increased expression levels, while Junos (transcript ID: XR_003955073.1, FC = 0.016) and another transcript of Snhg12 (transcript ID: ENSMUST00000126380, FC = 0.017) exhibited downregulated expression in FDM retinal tissue samples. The lncRNA OIP5-AS1 is involved in the pathogenesis of a variety of diseases, including colon cancer ( Wang Y. et al, 2021 ), prostate cancer ( Zhang Y. et al, 2021 ), papillary thyroid cancer ( Zhang X. et al, 2021 ), and osteosarcoma ( Li et al, 2021 ), as well as heart failure ( Zhuang et al, 2021 ). More importantly, previous evidence has suggested that OIP5-AS1 might participate in the mechanisms of primary open angle glaucoma (POAG) and cataracts ( Zhou et al, 2020 ) ( Jing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As MIAT also promotes tumorigenesis by binding AEG-1, a protein that affects diverse pathways [ 21 ], it is possible that NFKB signalling is a central lncRNA effector across diseases and tissues. Finally, no clear effector mechanism was defined for OIP5-AS1 during its female-specific cardioprotective role [ 22 ].…”
Section: Functions Of Recently Studied Long Noncoding Rnas In Cardiov...mentioning
confidence: 99%